LITERATURE RIVIEW : HUBUNGAN TINGKAT STRES, AKTIVITAS FISIK DAN PERILAKU KONSUMSI MAKANAN CEPAT SAJI TERHADAP KEJADIAN DISMENORE PADA REMAJA PUTRI - Shalia Permata (Jurnal Kesehatan, 2024)
Pain during menstruation is pain such as muscle spasms, cramps and throbbing which generally originates from the lower abdomen, and it occurs before and during menstruation. Primary dysmenorrhea is experienced by more than 50 percent of women and 10-15 percent of them experience severe pain that interferes with their daily activities and activities. Physical activity, consumption of fast food, and stress levels are factors that trigger dysmenorrhea. a daughter who has menstruated and has many impacts. Usually, young women who experience dysmenorrhea have high levels of stress and frequently consume fast food. The incidence of dysmenorrhea in each country is reported to be more than 50%. The prevalence of dysmenorrhea in Asia is 74.5%. Meanwhile, in Indonesia the incidence of dysmenorrhea is 64.25. The purpose of the Literature Review is to review to determine the relationship between physical activity, fast food consumption, and stress levels with the incidence of dysmenorrhea. Method Literature review was carried out based on issues, methodology, equations and further research proposals. Of the 5 used observational research methods with a cross-sectional research designResults Based on 5 studies, it was found that t shows a relationship between physical activity, fast food consumption, stress levels and the incidence of dysmenorrhoea. Conclusion from this study there is a relationship between age at menarche, fast food, stress and exercise and the incidence of dysmenorrhoea. Keywords: Dysmenorrhea, Junk Food, Stress, Young Women.